The perceived impact of leaders’ humility on team effectiveness: an empirical study - Rego, J. (2019)
We assess the perceived impact of leaders’ humility (both self and other-reported) on team effectiveness, and how this relationship is mediated by balanced processing of information. Ninety-six leaders (plus 307 subordinates, 96 supervisors, and 656 peers of those leaders) participate in the study. The findings suggest that humility in leaders (as reported by others/peers) is indirectly (i.e., through balanced processing) related to leaders’ perceived impact on team effectiveness. The study also corroborates literature pointing out the benefits of using other-reports (rather than self-reports) to measure humility, and suggests adding humility to the authentic leadership research agenda.